Having Children Intensifies Faith: A Mixed Method Study on How Parenthood Amplifies the Importance of Faith - Bjørntvedt, Andreas (Journal of empirical theology, 2025)
This study explores how parenthood impacts religious faith. Through a mixed-methods approach, the research examines how becoming a parent intensifies faith while simultaneously prompting critical reflection on childhood beliefs and religious practices. Participants expressed a strong desire to pass on faith traditions but also faced challenges in reconciling personal doubts and evolving perspectives. Parenthood serves as both a reaffirmation and intensifying of faith, but also a catalyst for questioning established beliefs. This is explored in a dialogue with McAdams life story theory and Heinz Kohut´s theory of the self. The study highlights the fluid nature of faith, emphasizing the role of parental reflection in shaping religious transmission across generations. This research contributes to understanding faith development from the parent’s perspective, a less-explored dimension in existing literature, and even the possible tension between the theologically charged imitatio (kenosis)-motif and the more sociological challenge of parental determinism.